A geographic distribution database of Mononychellus mites (Acari, Tetranychidae) on cassava (Manihot esculenta) - Vásquez Ordoñez, Aymer Andrés; Parsa, Soroush (Pensoft Publishers, 2014)
The genus Mononychellus is represented by 28 herbivorous mites. Some of them are notorious pests of cassava (Manihot esculenta Crantz), a primary food crop in the tropics. With the exception of Mononychellus tanajoa (Bondar), their geographic distribution is not widely known. This article therefore reports observational and specimen-based occurrence data of Mononychellus species associated with cassava. The dataset consists of 1,513 distribution records documented by the International Center for Tropical Agriculture (CIAT) between 1975 and 2012. The specimens are held at CIAT’s Arthropod Reference Collection (CIATARC). Most of the records are from the genus’ native range in South America and were documented between 1980 and 2000. Approximately 61% of the records belong to M. tanajoa, 25% to M. caribbeanae (McGregor), 10% to M. mcgregori (Flechtmann and Baker) and 2% to M. planki (McGregor). The complete dataset is available in Darwin Core Archive format via the Global Biodiversity Information Facility (GBIF).